Money income and wealth : the macroeconomics of a monetary economy - "Motley , Brain" (Delhi, 1982)
In Money Income and Wealth the emphasis is on policy. Theoretical models are in most cases illustrated by considering how they respond to changes in policy variables such as tax rates, the stocks of money and government bonds, and government expenditures. In addition, the analysis seeks to describe how these models behave as the economy moves from one equilibrium position to another as well as what those equilibria fool like when the economy reaches them.
Keywords: Macroeconomics